ANALYSIS OF ECONOMIC GROWTH, OPEN UNEMPLOYMENT RATE AND POVERTY RATE USING TECHNOLOGY - Elvina Safitri; Mukhlis Yunus; Ade Taufan; Hayati Hayati (Jurnal Ipteks Terapan (Research Of Applied Science And Education ), 2022)
This study examines the effect of economic growth and the open unemployment rate on the poverty rate in Merangin District, Jambi Province. The type of data used in this study is secondary data, the poverty rate from 2010-2018, economic growth from 2011-2018, and the open unemployment rate from 2011-2018. The data were obtained from the Central Bureau of Statistics of Merangin Regency, data analysis techniques used parametric statistical analysis methods and hypothesis testing using SPSS. The purpose of this study was to determine the effect of economic growth and the open unemployment rate on the poverty rate in Merangin District. Multiple linear regression data analysis was carried out through parametric statistical assumption testing and hypothesis testing, to see whether there are similarities that can predict the dependent variable, parametric assumption tests include (1) normality test, (2) multicollinearity test, (3) heteroscedasticity test, and ( 4) autocorrelation test. While the hypothesis testers are (1) Determinant Coefficient Test (R Square), and (2) T test. The results of this study indicate that economic growth has no significant effect on the poverty rate, while the open unemployment rate has a positive effect on the poverty rate in Merangin District, Jambi Province. The value of the determinant coefficient is 0.224 which means that the independent variable affects 22% of the dependent variable on the poverty level in Merangin Regency, Jambi Province.